Kepadatan Larva dan Karakteristik Kontainer Kasus Demam Berdarah di Wilayah Pesisir Kota Tegal - Nursanti, Aulia Dwi; Kusariana, Nissa; Wurjanto, Moh Arie; Martini, Martini (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
Backgound: Tegal is an endemic dengue fever city with high Incidence Rate (IR) as 38,4 per 100.000 population. The district with the highest number of DHF cases was Panggung Village, which is located in the coastal area and directly border with java sea. DHF cases are caused by the high scale of Density Figure (DF). this research was conducted to provide an overview of larval density, characteristics container, and practice level of dengue prevention programs (PSN) using spatial analysis tools. Method: The method used is observational descriptives with a cross-sectional study design. The sample size is 40, determined by simple random sampling including all DHF cases that occurred from January to September 2023. Result: The results of this study indicate that the 3 DHF cases were found. Aedes larva density level in Panggung Village reaching the intermediate level (DF 4) and RW 9 is the neighbourhood with the highest larva density (DF=6). The Charateristics of water container as follows such as house with more than 3 container, non-disposable site,ceramic and plastic, bright colour, artesian well, inside the house, open-mouthed that are larvae positive. 57,5% respondents at good level on dengue prevention practice. Spatial analysis found that 2 houses inside the 100 buffer area, distribution of temperature and pH on the container that are larvae positive are on the range of 25-300C and 7-9 pH level, distribution of DHF cases is dispersed (ANN>1) with 369,09 meters distances between the case. Conclusion: Dengue transmission in Panggung Village is at an intermediate level, caused by dengue vector migration. Keywords: Larval Density, Container Charactheristics, DHF